Prevalence of prediabetes in children and its association with risk factors - Aroor, Amitha Rao; Varghese, Tharun C.; Soans, Santosh T. (International Journal of Contemporary Pediatrics, 2019)
Background: Type 2 Diabetes is becoming more common at younger age group. It is important to screen children and adolescents for prediabetes to prevent long-term complications of diabetes. This study was conducted to study the prevalence of prediabetes in children and its association with risk factors Methods: It is a Prospective hospital-based study. Children aged 6 to 18 years admitted in the Pediatric ward of tertiary care hospital were included. Study was done over a period of 2 years November 2015-October 2017. Participants were screened to find out the prevalence of prediabetes. Prediabetes was defined as fasting glucose concentration (FBS)of 100-125 mg/dl or a HbA1c value of between 5.7% and 6.4%, or a two-hour post-glucose tolerance concentration (OGTT) of 140-199mg/dl. Results: 607 children participated in the study.56.3% were males. Prevalence of Prediabetes was 20.4% with a combination of OGTT, FBS and HbA1c tests. Prevalence by OGTT was 5.9%, HbA1c 4.1% and by FBS was 17.1%. Higher prevalence of prediabetes was associated with male gender, frequent consumption of junk foods, decreased physical activities, overweight, obesity and high waist to hip ratio. Combination of FBS with GTT and FBS with HbA1c had better sensitivity and specificity when compared to combination of OGTT with HbA1c . Conclusion: Screening of children for prediabetes at younger age especially those with risk factors and intervention with lifestyle modification may help in delaying the progression of the disease.